On Modeling Laminar Flow Through Variable Permeability Transition Layer - M. S. Abu Zaytoon; M. H. Hamdan (Fluids)
A generalized model of the variable permeability in the transition layer is introduced in this work. This model can handle flows with a small Darcy number and might be useful in controlling permeability amplifications. A solution method for the resulting inhomogeneous, generalized Airy equation is presented, together with a computational procedure for evaluating the generalized Airy functions and the generalized Nield–Kuznetsov function of the first kind. A complete solution is then provided for the tri-layer flow problem that involves flow over a porous layer with an embedded transition layer.